2009
DOI: 10.1093/hmg/ddn429
|View full text |Cite
|
Sign up to set email alerts
|

Association of ESR1 gene tagging SNPs with breast cancer risk

Abstract: We have conducted a three-stage, comprehensive single nucleotide polymorphism (SNP)-tagging association study of ESR1 gene variants (SNPs) in more than 55,000 breast cancer cases and controls from studies within the Breast Cancer Association Consortium (BCAC). No large risks or highly significant associations were revealed. SNP rs3020314, tagging a region of ESR1 intron 4, is associated with an increase in breast cancer susceptibility with a dominant mode of action in European populations. Carriers of the c-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 10 publications
2
64
1
Order By: Relevance
“…Examining the PvuII polymorphism first, only 13 studies to date have investigated the relationship between the PvuII polymorphism and breast cancer risk, and all of these studies were in Hardy-Weinberg equilibrium (Yaich et al, 1992;Cai et al, 2003;Shin et al, 2003;Wedren et al, 2004;Lu et al, 2005;Onland-Moret et al, 2005;Shen et al, 2006;Hu et., 2007;Kjaergaard et al, 2007;Gonzalez-Mancha et al, 2008;Gonzalez-Zuloeta et al, 2008;Dunning et al, 2009). Except for the model ('CC' vs. 'CT+TT', P = 0.008), there was little evidence of statistical heterogeneity.…”
Section: Meta-analysis Of the Esr-α Polymorphisms And Breast Cancer Riskmentioning
confidence: 98%
See 1 more Smart Citation
“…Examining the PvuII polymorphism first, only 13 studies to date have investigated the relationship between the PvuII polymorphism and breast cancer risk, and all of these studies were in Hardy-Weinberg equilibrium (Yaich et al, 1992;Cai et al, 2003;Shin et al, 2003;Wedren et al, 2004;Lu et al, 2005;Onland-Moret et al, 2005;Shen et al, 2006;Hu et., 2007;Kjaergaard et al, 2007;Gonzalez-Mancha et al, 2008;Gonzalez-Zuloeta et al, 2008;Dunning et al, 2009). Except for the model ('CC' vs. 'CT+TT', P = 0.008), there was little evidence of statistical heterogeneity.…”
Section: Meta-analysis Of the Esr-α Polymorphisms And Breast Cancer Riskmentioning
confidence: 98%
“…A total of 11 studies were included in the meta-analysis performed to examine the associations between the XbaI polymorphism and breast cancer risk; four studies of these were not consistent with Hardy-Weinberg proportions (Cai et al, 2003;Shin et al, 2003;Wedren et al, 2004;Lu et al, 2005;Onland-Moret et al, 2005;Shen et al, 2006;Hu et., 2007;Gonzalez-Zuloeta et al, 2008;Dunning et al, 2009). Since there is heterogeneity in model ('G' vs. 'A'), random-effects analysis was selected.…”
Section: Meta-analysis Of the Esr-α Polymorphisms And Breast Cancer Riskmentioning
confidence: 99%
“…1B) and is located on chromosome 6 at 6q25.1 (19), a susceptibility locus identified as particularly important for breast cancer in Chinese women in a recent genome-wide association study (20). Genotypic polymorphism of ESR1 has long been reported to be important in determining breast cancer susceptibility (21)(22)(23)(24)(25)(26). However, the results have been inconsistent and the molecular mechanisms by which these polymorphisms affect the function of ERα remain unclear.…”
mentioning
confidence: 99%
“…Most published association studies have evaluated the most common SNPs of ERα: PvuII (397T > C, rs2234693) and the XbaI (351A > G, rs9340799) restriction fragment length polymorphisms, both located in intron 1 and found to be in LD [179]. There are mixed results for these two SNPs reported from several studies [180][181][182][183][184][185][186][187]. In a meta-analysis of AA genotype of XbaI (rs9340799) [188].…”
Section: Previous Literaturementioning
confidence: 99%
“…Although its functionality is not well established, this region seems to alter the ERα expression [189]. A meta-analysis, conducted by Li and colleagues [188], pooled data from three studies [180,[182][183] and no association was observed (estimate not given). Lastly, two studies have reported an increase in risk: a small study (n=192) conducted in Romania [189] reported a >2-fold increase in risk (per-allele); and a study conducted in the United Kingdom with ~3,900…”
Section: Previous Literaturementioning
confidence: 99%